Chromatic disorder in Trachops cirrhosus (Spix, 1823) (Chiroptera: Phyllotomidae) on Ecuadorian Amazon - Bravo-Salinas, Ronald (2022)
We present a case of chromatic disorder observed in a specimen of Trachops cirrhosus from lowland forests of the Ecuadorian Amazon. During the field work, six individuals of this species were captured with mist nets in an intervened habitat, of which, a juvenile male specimen was distinguishable from the rest of the individuals due to the presence of whitish spots on the ventral region, on the chest and abdomen. We discuss the previous reports of this type of pigmentary disorders in bats from Ecuador, and in the Neotropic, documenting the first record of Trachops cirrhosus with this condition for the country.